Tingkat Kepatuhan Protokol Kesehatan Masyarakat dalam Menerapkan Aturan Kesehatan Semasa Pandemi Covid-19 - Wahyudin Wahyudin; Andhika Lungguh Perceka (Jurnal Medika Cendikia, 2021)
Corona virus can infect the human airway, so it can cause small to severe obstacles even causing death. Medical rules or health health rules are maintenance instructions before going to the hospital getting approval by the head of health EMS (Emergency Medical Service) in the area of residence, which is utilized in considering emergency stuasi on the ground by outlining the permitted and appropriate medical care that can be provided by emergency medical service personnel to patients experiencing medical emergencies. . This study has a direction that is to understand the level of public obedience about health rules during covid 19 outbreak with journal review methods. This study is reviewed through a google scholar database, to find journals that conform to predetermined exclusion inclusion standards. From the study of 3 articles found that the obedience of the community 46.2% during emigrants is quite good and 53.8% do not obey the health rules due to age, gender & education factors.